The three‐dimensional structure of VIM‐31 – a metallo‐β‐lactamase from Enterobacter cloacae in its native and oxidized form. (13th April 2015) - Kupper, Michaël B.; Herzog, Konrad; Bennink, Sandra; Schlömer, Philipp; Bogaerts, Pierre; Glupczynski, Youri; Fischer, Rainer; Bebrone, Carine; Hoffmann, Kurt M.
<x xml:space="preserve">Abstract</x> The metallo‐β‐lactamase VIM‐31 differs from VIM‐2 by only two Tyr224His and His252Arg substitutions. Located close to the active site, the Tyr224His substitution is also present in VIM‐1, VIM‐4, VIM‐7 and VIM‐12. The VIM‐31 variant was reported in 2012 from Enterobacter cloacae and kinetically characterized. It exhibits globally lower catalytic efficiencies than VIM‐2. In the present study, we report the three‐dimensional structures of VIM‐31 in its native (reduced) and oxidized forms. The so‐called 'flapping‐loop' (loop 1) and loop 3 of VIM‐31 were not positioned as in VIM‐2 but instead were closer to the active site as in VIM‐4, resulting in a narrower active site in VIM‐31. Also, the presence of His224 in VIM‐31 disrupts hydrogen‐bonding networks close to the active site. Moreover, a third zinc‐binding site, which also exists in VIM‐2 structures, could be identified as a structural explanation for the decreased activity of VIM‐MBLs at high zinc concentrations.